Development of robot simulation software for five joints mitsubishi RV-2AJ robot using MATLAB/Simulink and V-Realm Builder. - Jambak, Muhammad Ikhwan; Haron, Habibollah; Nasien, Dewi (2008)
The Robot Simulation Software (RSS) nowadays is paramount important to increase the accuracy and efficiency of industrial robot. This paper reports the development of the RSS where a Mitsubishi RV-2AJ robot has been taken as a case study. The project adopts the virtual reality interface design methodology and utilizes MATLAB/Simulink and V-Realm Builder as the tools. A robot model has been developed and a RSS software life cycle has been implemented.